Solid Fuel from Decanter Cake: A Preliminary Study - Mohd Husin, Mohd Haizal (2009)
Decanter cakes are the major wastes in crude palm oil industry which are currently disposed in the landfill or reuse as fertilizer. But on other side, decanter cakes has potentially as a solid fuel same as a charcoal or wood briquette, based on their calorific value cause of the residual oil in decanter cakes. This paper presents the initial findings of a thermogravimetric analysis (TGA) and heat of combustions by using oxygen bomb calorimeter methods for characterizing the different pyrolyzed decanter cakes (PDC). Meanwhile, the actual heat transferred value technique for comparing potential decanter cake with commercial solid fuel types, charcoal, coconut charcoal and charcoal briquette. Observation about flame, duration time of burning process and ash contents also will take out for comparison.